Lung epithelial and alveolar macrophage-like cell interactions significantly modify innate responses to bacterial endotoxin with the involvement of direct cellular contacts, TNF-α, ICAM1 and MCP-1 - Wood, Connor; Khera, Shagun; Woo, Minjeong; Sharma, Vikram; Lopatecka, Justyna; Coulon, Frederic; Nasir, Zaheer; Delorme, Vincent; Jackson, Simon K.; Fejer, György (Frontiers in Immunology, 2026)
IntroductionLung alveolar macrophages (AMs) and epithelial cells form the first line of defense against inhaled pathogens. Their interactions strongly influence innate immune responses in the lung, yet the mechanisms underlying this cross-talk remain incompletely understood.MethodsIn this study, we established a co-culture system using a primary model of AMs (MPI alveolar macrophage-like cells) and MLE-12 alveolar epithelial cells to investigate innate responses and cellular interactions during bacterial lipopolysaccharide (LPS)-induced TLR4 activation.ResultsCytokine and chemokine profiling revealed that co-cultures exhibited significantly enhanced proinflammatory responses to both LPS and TLR2 ligands—including IL-6, TNF-a, and MCP-1 secretion—compared with mono-cultures. Strikingly, we identified MLE-12 epithelial cells as a source of lipopolysaccharide-binding protein (LBP), which is essential for LPS recognition in AMs and MPI alveolar macrophage-like cells. LBP secretion by epithelial cells explained cytokine responses to LPS under serum-free conditions; however, additional mechanisms—apparent in the presence of serum/LBP—also contributed to the amplified co-culture responses. These mechanisms included direct cell–cell contacts, as conditioned media from unstimulated cells failed to reproduce similar effects in mono-cultures. Moreover, co-cultures of naïve MPI cells and inflamed epithelial cells (MLE-12 cells pretreated with media from activated MPI macrophages) were found to release a nonnegligible amount of chemokines, even in the absence of LPS. This demonstrated an inflammatory amplification loop mediated by both contact dependent and soluble factors. Phospho-flow cytometry further revealed coculture- specific signaling, with enhanced MAPK pathway activation in macrophages and NF-kB activation in epithelial cells. Finally, LPS-activated MPI alveolar macrophage-like cells induced TNF-a–dependent ICAM-1 expression and apoptosis in MLE-12 cells. Increased ICAM-1 expression, in turn, promoted MCP-1 production in epithelial cells in an ICAM-1–dependent and cell contact mediated manner.DiscussionTogether, these findings identify cellular contacts and a TNF-a–ICAM-1–MCP-1 axis—supported by epithelial-derived LBP—as key drivers of innate immune synergy between lung alveolar macrophages and epithelial cells. Our results establish the MPI–MLE-12 co-culture as a tractable model for dissecting pulmonary innate immune mechanisms.